Use of Management Control as a Stimulus for Organizational Resilience: Single-Entity Survey in a Petroleum Derivatives Company - Bragueto Martins, Daiana; Frezatti, Fábio (Advances in Scientific and Applied Accounting, 2023)
Purpose: The paper aims to investigated how the use of the Management Control System influences in the management of organizational resilience in a Brazilian company. Method: A survey single entity developed in a Brazilian oil derivative trading company with structure, size and management control system required for the research. The data were collected based on a questionnaire sent to executives from different department For data analysis, the structural model was estimated using the partial least squares method (PLS-PM - Partial Least Squares Path Modeling). Results: The results support the hypothesis that the use of the management control system has a positive impact on the strategic. Thus, it was observed that high levels of the use of the management control system in the forms of beliefs systems, boundary systems, diagnostic control system and interactive control system increase the organization's capacity for resilience by acting in a proactive way, with strategic vision facing the business context's adversities, providing the strategic renewal proposed by Simons (1995). Contributions: The theoretical contribution lies in the development of a model that aims to assist organizations in managing organizational resilience through management control systems. The use of the priority map for data analysis brought a practical point of view, this helps managers to decide which pattern of control best fits the circumstances in which they operate and their strategic challenges, contribute to understanding how the use of management control system impacts on the resilience in the organizational environment.